Development and Validation of a Risk Assessment Tool for Gaming Disorder in China: The Gaming Hazard Assessment Scale - Tang, Ying; Liao, Zhenjiang; Huang, Shucai; Hao, Jingyue; Huang, Qiuping; Chen, Xinxin; Lin, Shuhong; Li, YiFan; Qi, Jing; Shen, Hongxian (Frontiers in Public Health, 2022)
Despite the growing research interest in gaming disorders, risk screening tools developed specifically for the Chinese population are still lacking. This study aimed to construct a screening tool to evaluate the risk of Gaming disorder (GD) development by assessing the severity of GD symptoms among Chinese gamers, based on clinical expert interviews, structured interviews with GD patients, a background literature review, and IGD/GD criteria proposed by the DSM-5 and ICD-11. It introduced the Gaming Hazard Assessment Scale—a multidimensional GD risk screening tool—and evaluated the dimension structure, reliability, and validity of the scale among 959 Chinese gamers. A three-level structure consisting of 18 items scored ranging from 0 to 54 ultimately indicated satisfactory reliability, good validity, and acceptable model fit. The scale will help to realize large-scale initial screening and early identification of patients with high risk of GD. Further evaluation of the Gaming Hazard Assessment Scale in clinical settings is highly recommended.